The effect of squat training with different eccentric contraction tempos on lower limb muscle strength - Mushuai Hao; Haonan Qi; Liang Zhao; Wei Han (PLoS ONE, 2026)
Objective This study aims to investigate the impact of 8-week squat training with different eccentric contraction tempos on maximal squat strength, jump height, and sprint performance among university students majoring in sports training. Methods Thirty participants were randomly assigned to either the 4/0/X/0 group, the 2/0/X/0, or the self-selected eccentric, isometric and inter-repetition tempo group (V/V/X/V), performing tempo-specific loaded squat training twice weekly for 8 weeks. Maximal squat strength, 30-meter sprint performance, countermovement jump (CMJ), and squat jump (SJ) heights were assessed before and after the intervention. A two-way repeated-measures ANOVA and effect size analysis were used to evaluate the training outcomes. Results 1) For maximal squat strength, no statistically significant inter-group difference was detected (P > 0.05). All three groups exhibited significant within-group improvements relative to baseline (P < 0.05 to P < 0.01). Descriptive effect size analysis showed the magnitude of improvement ranked as follows: 2/0/X/0 group (ES = 1.45)> V/V/X/V group (ES = 0.85)> 4/0/X/0 group (ES = 0.64). 2) For CMJ height, both the 2/0/X/0 and V/V/X/V groups showed significant improvement compared to pre-intervention (P < 0.05), while the 4/0/X/0 group exhibited a significant decrease (P < 0.01). ES magnitudes followed the order: 2/0/X/0 group (ES = 1.07) > V/V/X/V group (ES = 0.30) > 4/0/X/0 group (ES = −0.90). 3) SJ height results mirrored CMJ trends, with ES values ranking:2/0/X/0 group (ES = 1.09) > V/V/X/V group (ES = 0.34) > 4/0/X/0 group (ES = −0.83). 4) In 30-meter sprint performance, the 2/0/X/0 group demonstrated significant improvement (P < 0.05), the 4/0/X/0 group showed significant decline (P < 0.01), and the V/V/X/V group exhibited no significant change. Effect sizes indicated significant improvement in the 2/0/X/0 group (ES = −0.76), no meaningful change in the V/V/X/V group (ES = −0.10), and a significant decline in the 4/0/X/0 group (ES = 0.63). Notably, despite significant gains in maximal strength, the 4/0/X/0 group displayed concurrent decrements in stretch-shortening cycle-based explosive performances. Conclusion Compared with the 4/0/X/0 and V/V/X/V tempos, the 2/0/X/0 tempo showed the most favorable improvement trend in lower-limb maximal strength, and induced significantly greater enhancements in explosive power performance.